Pentingnya Penerapan Literasi Membaca untuk Meningkatkan Berbahasa dan Menulis Bagi Anak Usia Dini - Hotmaria Panjaitan; Katrina Silitonga; Rodearni Hutahaean; Mei Lastri Butar butar (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
This article discusses the importance of implementing reading literacy for early childhood in improving language and writing skills. Reading literacy is the ability to understand and use written texts in everyday life. The application of reading literacy in early childhood has significant benefits in developing children's language and writing skills.In this article, we will explain why reading literacy is important for young children. Apart from that, we will also discuss the benefits that children gain in developing language and writing skills through the application of reading literacy. Finally, this article will provide several practical strategies and suggestions for parents and educators to implement reading literacy in early childhood.In conclusion, implementing reading literacy in early childhood is very important in improving children's language and writing skills. By introducing children to reading literacy from an early age, children will have a strong foundation in understanding written texts, develop language skills, and improve writing abilities. It is hoped that this article will provide useful insights for parents and educators in understanding the importance of reading literacy for early childhood.